Improved Convergence Analysis of Gauss-Newton-Secant Method for Solving Nonlinear Least Squares Problems - Ioannis Argyros; Stepan Shakhno; Yurii Shunkin (Mathematics, 2019)
We study an iterative differential-difference method for solving nonlinear least squares problems, which uses, instead of the Jacobian, the sum of derivative of differentiable parts of operator and divided difference of nondifferentiable parts. Moreover, we introduce a method that uses the derivative of differentiable parts instead of the Jacobian. Results that establish the conditions of convergence, radius and the convergence order of the proposed methods in earlier work are presented. The numerical examples illustrate the theoretical results.